Measuring Homelessness: Implications for Policy - O’Sullivan, Eoin (Κοινωνική Πολιτική, 2021)
Who we define as experiencing homelessness and how we research the experience of homelessness may seem technical matters for statisticians and researchers to agree on rather than matters of public policy. In this paper I argue that the way in which we collect data on homelessness and how that data is presented has significant implications for the framing of homelessness, with the majority of countries measuring homelessness at a point-in-time, which provide little information on the dynamics of homelessness. Using the example of the Republic of Ireland, we can see that the stock and flow data on homelessness show very different patterns of the experience of homelessness, with the number of adults in emergency accommodation at a point- in-time is determined by the numbers entering emergency accommodation, the length of time in emergency accommodation and the rate at which exits occur.